THE IMPACT OF BOARD CHARACTERISTICS ON FIRM PERFORMANCE OF FTSE 100 LISTED UK FIRMS - Obirieze, Leticia/C (2022)
ABSTRACT The widespread corporate scandals that engulfed many firms globally have necessitated instituting adequate corporate governance measures by establishing appropriate board structure for corporations. Ample evidence from empirical studies has validated the importance for firms to promote the establishment of suitable board characteristics to enhance firm value. This study explored the board characteristics of board size, board independence, director ownership, board diversity and CEO duality. It adopted an accounting-based performance measure of return on assets (ROA). In general, this study examines the impact of the various board characteristics on firm performance. This research aims to investigate the effect of board diversity on firm performance, examine the influence of board size on corporate performance, ascertain the impact of CEO duality on firm performance and probe the extent to which firm performance is influenced by directors share ownership. Based on prior literature, this study employed quantitative data from FAME database and annual reports from websites of FTSE 100 firms in the UK spanning from 2018 to 2020. The study sample involved only non-financial firms. The hypothesis was empirically tested using multiple linear regression analysis on STATA software. The findings indicated that board size, board independence and director share ownership have a nonsignificant correlation with firm performance. In addition, the result of CEO duality suggests a significant positive relationship. In contrast, board nationality and gender diversity disclose a crucial positive association with firm performance. Board age on the other hand, reveals a meaningful negative relationship. On the grounds of these results, it is recommended that firms incorporate elements of board diversity (nationality and gender) into board composition to enhance corporate performance. The sample size employed for this study was 64 non-financial firms thus, it is illogical to deduce that it is a representative of listed firms in the UK.